Understanding of the structural chemistry in the uranium oxo-tellurium system under HT/HP conditions - Hao, Yucheng; Langer, Eike M.; Xiao, Bin; Kegler, Philip; Cao, Xin; Hu, Kunhong; Eichel, Rüdiger-A.; Wang, Shuao; Alekseev, Evgeny V. (Frontiers in Chemistry, 2023)
The study of phase formation in the U-Te-O systems with mono and divalent cations under high-temperature high-pressure (HT/HP) conditions has resulted in four new inorganic compounds: K2[(UO2)(Te2O7)], Mg[(UO2)(TeO3)2], Sr[(UO2)(TeO3)2] and Sr[(UO2)(TeO5)]. Tellurium occurs as TeIV, TeV, and TeVI in these phases which demonstrate the high chemical flexibility of the system. Uranium (VI) adopts a variety of coordinations, namely, UO6 in K2[(UO2)(Te2O7), UO7 in Mg[(UO2)(TeO3)2] and Sr[(UO2)(TeO3)2], and UO8 in Sr[(UO2)(TeO5)]. The structure of K2[(UO2)(Te2O7)] is featured with one dimensional (1D) [Te2O7]4- chains along the c-axis. The Te2O7 chains are further linked by UO6 polyhedra, forming the 3D [(UO2)(Te2O7)]2- anionic frameworks. In Mg[(UO2)(TeO3)2], TeO4 disphenoids share common corners with each other resulting in infinite 1D chains of [(TeO3)2]4- propagating along the a-axis. These chains link the uranyl bipyramids by edge sharing along two edges of the disphenoids, resulting in the 2D layered structure of [(UO2)(Te2O6)]2-. The structure of Sr[(UO2)(TeO3)2] is based on 1D chains of [(UO2)(TeO3)2]∞2− propagating into the c-axis. These chains are formed by edge-sharing uranyl bipyramids which are additionally fused together by two TeO4 disphenoids, which also share two edges. The 3D framework structure of Sr[(UO2)(TeO5)] is composed of 1D [TeO5]4− chains sharing edges with UO7 bipyramids. Three tunnels based on 6-Membered rings (MRs) are propagating along [001], [010] and [100] directions. The HT/HP synthetic conditions for the preparation of single crystalline samples and their structural aspects are discussed in this work.